Високоефективнi телурид-кадмiєвi детектори X- i y-випромiнювання - Maslyanchuk, O. L.; Aoki, T.; Sklyarchuk, V. M.; Melnychuk, S. V.; Kosyachenko, L. A.; Grushko, E. V. (Publishing house "Academperiodika", 2018)
Electric parameters of chlorine-doped CdTe crystals with a resistivity of (3÷6)× ×10^9 Ω·cm have been studied. The heavily doped material was characterized by an almost intrinsic conductivity, which is explained on the basis of the charge-carrier statistics by an emergence of self-compensated complexes. The ionization energy and the compensation degree of the impurity responsible for the semiinsulating state of CdTe are determined. The reverse current-voltage characteristics of the Ni/CdTe/Ni structure with a Schottky diode are interpreted as those of X/y-radiation detectors with extremely low values of “dark” currents of about 5 nA at a voltage of 1500 V and a Schottky contact area of 0.1 cm2 (at 300 K). Results testifying to a detector energy resolution of 0.42% for the spectrum of 137Cs isotope at an applied voltage of 1200 V and a temperature of 300 K have been reported. The dependence of the detection efficiency on the concentration of noncompensated impurities (defects) N, which determines the width of the space charge region in the diode, is proved to be described by a function with a maximum located at N ≈ 2×1011 cm^−3 for 137Cs isotope. By comparing the spectra obtained while irradiating the detector from either the Schottky or ohmic contact side, the concentration of noncompensated impurities in the studied crystals (of about 1012 cm^−3) is determined, which is close to the optimum N value.